Design, synthesis and characterization of 2,4-disubstituted-1,3 thiazole amino acid derivatives towards its applications on antimicrobial and antioxidant activities - Ngah, Nurziana; Darnis, Deny Susanti; Abd Hamid, Shafida; Jumal, Juliana; Abdullah Ripain, Iswatun Hasanah (2018)
The study on small molecule of heterocyclic incorporated with nitrogen and sulfur have been widely explored in term of their synthetic and biological applications. Heterocyclic thiazole emerges as one of the most frequently reported in those field. Since thiazole moiety seems to be possible candidate in various biologically active agents, we developed several new thiazole derivatives by the reaction of haloketone, ammonium thiocyanate and selected amines which give corresponding thiazole derivatives in excellent yields. The chemical structures of the resulting products were confirmed by means of 1H NMR, IR, UV-Vis and GCMS. These compounds were screened for antibacterial properties against Gram-positive bacterial strains namely Bacillus cereus, Staphylococcus epidermidis as well as Gram-negative bacterial strains such as Escherichia coli and Pseudomonas aeruginosa using disc diffusion method. Molecular docking was also performed against Glucosamine-6-phosphate (GlcN-6-P) synthase which is known as the essential building block of most bacteria in order to know the detailed mechanism.